Building facade painting complex process multicriteria evaluation/Fasadų dažymo daugiakriterinis vertinimas tinklinio modelio mazgų „išpjovimo” ir sprendimų daugiapakopės sintezės metodais - Janušaitis, Rolandas; Liubinskaitė, Rima (Journal of Civil Engineering and Management, 2001)
Today there are many multicriteria evaluation methods used in building projects. They enable to make component (complex) evaluations of the task. Before a multicriteria evaluation of building facade complex process we develop a technological network model which represents technological systems and work performance variants graphically. We use technological network model junctions “cut” method for finding faster final result, for reducing alternative decisions number and facilitating calculations. This method permits to reject not irrational variants from calculations. Facade painting model consists of the following partial processes: surface preparing, priming, putting and painting. Making multicriteria decisions synthesis all these processes are interpreted as stages. It’s necessary to determine the importance of each stage with respect to another stage (stage significance). To find stage significance it’s possible to use expert, pair comparison methods, etc. Each stage consists of a certain number of alternatives. For comparison and evaluation of these alternatives, we produce a system of criteria (technical-economical indicators and qualitative characteristics). Using technological network junctions “cut” method, decision multistage synthesis method and carrying out multicriteria evaluation, it is possible to make a more precise alternative decisions analysis, evaluating the stage significance. This is very important for customers, contractors, projectors, etc. Article in Lithuanian. First Published Online: 30 Jul 2012